PRINCIPAL'S PROGRAM IN IMPROVING THE PROFESSIONALISM OF ARABIC TEACHERS - Ira Aniati; Yudistira Yudistira (UNiversitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
Teacher professionalism affects the success or failure of learning, and a great principal affects the quality of schools. The problem of this research is to know the principal’s program to improve the professionalism of Arabic teachers, and to gain knowledge about tips for success in teaching arabic. The objectives of this research are to show how the head of the school program qualifies Arabic language teachersKeyword: Principal Program, Arabic Teacher Professionalism. This type of research is a qualitative research with descriptive method by using study literature. The results of the research related programs carried out by a principal are managing and developing the teaching profession, supporting the teachers in scientific activities and teacher organizations, and supervising administration and visiting classes. The conclusion of this research is the neutralization of the school head's program to qualify Arabic language teachersTeacher professionalism affects the success or failure of learning, and a great principal affects the quality of schools. The problem of this research is to know the principal’s program to improve the professionalism of Arabic teachers, and to gain knowledge about tips for success in teaching arabic. This type of research is a qualitative research with descriptive method by using study literature. The results of the research related programs carried out by a principal are managing and developing the teaching profession, supporting the teachers in scientific activities and teacher organizations, and supervising administration and visiting classes. برنامج رئيس المدرسة لتأهيل مدرسي اللغة العربيةتؤثر الحرفانية لدى المدرسين على نجاح أو فشل التعليم، ويؤثر رئيس المدرسة الممتاز على جودة المدرسة. المسألة الأساسية في هذا البحث هي اكتشاف برنامج رئيس المدرسة في تأهيل مدرسي اللغة العربية واكتساب المعلومات عن مفتاح النجاح في دراسة اللغة العربية. الهدف من هذا البحث هو لبيان كيف برنامج رئيس المدرسة لتأهيل مدرسي اللغة العربية. المنهج الذي تستخدم في هذا البحث هو المنهج الوصف. وتستخدم الباحثة البحث المكتبى. ونتائج البحث من البرامج المحاولة هي تدبير وتطوير مهنة المدرس، وحث المدرس للمشاركة في الأنشطة العلمية ومنظمة المدرسين، ومراقبة الإدارة وزيارة الفصل. الخلاصة من هذا البحث هي تحيد برنامج رئيس المدرسة لتأهيل مدرسي اللغة العربية.